Elucidation of the WNT & AKT/Phosphoinositide-3-Kinase Pathways in Colorectal Carcinoma - Khor, Tin Oo (2004)
Colorectal cancer (CRC) is the third most common cancer III Malaysia and is currently the commonest cancer in males. Genetics, experimental and epidemiological data suggest that CRC develops from complex interaction between inherited susceptibility and environmental factors. Accumulating evidence suggests that the Wnt and PI3K (phosphoinositide-3-kinase)/Akt signalling pathways playa causative role in tumorigenesis of colorectal cancer. By employing immunohistochemical method, the expressIOn and correlation of several key regulators or related biomolecules of the Wnt and PI3K1Akt signalling pathways in 47 archival formalin fixed, paraffin embedded tissues of surgically resected colorectal cancer (CRC) specimens performed at Kuala Lumpur Hospital (KLH) between 1999 and 2000, were studied. Laser captured microdissection technique, polymerase chain reaction and direct sequencing were used to investigate mutations in exon 3 of the p-catenin gene. Mutations in the mutation cluster region (MCR) of adenomatous polyposis coli (APC) gene were also investigated. The expressions of Wnt-l, WISP-l and FRAT-l mRNA were determined by reverse-transcription and real-time polymerase chain reaction method. The results showed that: The expressions ofWnt-l, FRAT-I, APC, nuclear p-catenin, cytoplasmic p-catenin, membrane p-catenin, membrane E-cadherin, cytoplasmic E-cadherin, WISP-I, cyclin-Dl, p-Aktl (Ser473), p-Akt1l2/3 (Thr308), p-BAD (Ser136), p-GSK 3p(Ser9) and survivin were found in 55.3%, 36.2%, 51.1% 44.6%, 95.7%,30.6%,46.8%,95.7%,31.9%, 10.6%,34%,44.7%,57.4% 44.7% and 59.6% of CRC tissues, respectively and 17.5%, 5% 100%, 0%, 75%, 100%, 100%, 50%, 12.5%, 0%, 5%, 12.5%, 22.5%, 22.5% and 32.5% of apparently normal adjacent tissues, respectively. The sum of scores for all biomolecules except APC, membrane p-catenin and membrane E-cadherin staining was significantly higher in CRC tissues in comparison to apparently normal adjacent tissues (p < 0.05). The sum of score for APC, membrane p-catenin and membrane E-cadherin staining was significantly lower in CRC tissues in comparison to apparently normal adjacent tissues (p < 0.05). The expression of Wnt and PI3K1Akt signalling pathway-related biomolecules was interrelated. The results ofnucleotide sequencing showed that no mutations at exon-3 of p-catenin were found. However, point mutations in the mutation cluster region of the APC gene leading to the formation of truncated APC protein, were found in four out eleven CRC tissues examined. A 1.43 to 21.26-foid and 1.11 to 109.14-fold increase in the level of expression of Wnt-l and FRAT-1 mRNA was found in eight out of eleven CRC tissues relative to apparently normal adjacent tissues. On the other hand, a 1.94 to 46.69-fold increase in the level of WISP-I mRNA was found in all the CRC tissues. This study has provided important information for researchers and clinicians in terms of clinical evidence of the involvement of the Wnt signalling pathway and PI3K1Akt signalling pathway in colorectal tumorigenesis. In addition, the present study also provided crucial information on the elucidation of the relationship between the biomolecules of these signalling pathways towards understanding their roles in colorectal tumourigenesis and the identification of potential targets for advance therapeutic intervention ofCRe. Based on our current results, we propose that Wnt-I, FRAT-1 and WISP-I could be served as potent therapeutic target for the treatment of CRe. On the basis of our present study, we conclude that the Wnt and PI3K1Akt signalling pathways are involved in tumourigenesis of CRC in Malaysia. These pathways are interrelated although they might also act independently in promoting tumour growth and inhibition of apoptosis. This study has also provided useful information for the search or design of better antitumour interventions.